Digital Inclusivity In EFL Oracy Development: Implementing The Multimodal Cognitive Oracy Model For Arabic Learners In Online Higher Education - V S Sreelakshmi; S Vijayakumar; M Ahamedullah; A Sathikulameen (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Inclusive education in English as a Foreign Language (EFL) has become increasingly critical in online higher education, particularly for Arabic-speaking learners who face unique linguistic challenges in developing oracy skills. This study evaluates the effectiveness of the Multimodal Cognitive Oracy Model (MCOM) in enhancing listening and speaking competencies among Arabic learners at B.S. Abdur Rahman Crescent Institute of Science and Technology, School of Arabic and Islamic Studies. A mixed-methods quasi-experimental design was employed with Arabic-speaking EFL learners enrolled in online degree programs. Participants were divided into experimental and control groups, with the experimental group receiving instruction through the MCOM framework incorporating computer-assisted language learning (CALL) tools, multimodal inputs (audio, visual, textual, kinesthetic), and cognitive scaffolding strategies. The eight-week intervention integrated authentic English materials, synchronous and asynchronous interactive activities, and formative feedback mechanisms. Data collection included pre- and post-intervention assessments of listening comprehension and speaking proficiency, supplemented by qualitative feedback through questionnaires and reflective journals. Results demonstrated statistically significant improvements in both listening comprehension and speaking fluency for the experimental group. Participants exhibited enhanced phonological awareness, improved pronunciation accuracy, increased oral communication confidence, and better comprehension of varied English accents. Qualitative analysis revealed high learner engagement and satisfaction with multimodal activities. Visual and auditory scaffolding effectively addressed L1 interference and facilitated cognitive processing of English phonemes. The study confirms that the Multimodal Cognitive Oracy Model provides an effective, inclusive pedagogical framework for Arabic-speaking EFL learners in online contexts. Practical implications emphasise curriculum integration of technology-enhanced oracy activities, educator training in CALL methodologies, and institutional digital infrastructure investment. Future research should explore longitudinal impacts and cross-cultural applications of the MCOM framework.